Answer :

Let p(x) = ax^{2} + 5x + b

As (x – 3) and are factors of p(x) hence each will divide p(x) leaving remainder as 0

Let us use the remainder theorem which states that if (x – a) divides a quadratic polynomial p(x) then p(a) = 0

⇒ p(3) = 0

Substituting x = 3

⇒ a(3)^{2} + 5(3) + b = 0

⇒ 9a + 15 + b = 0

⇒ b = – 9a – 15 …(ii)

And also

Substituting

Multiplying throughout by 9

⇒ a + 15 + 9b = 0

⇒ –9b = a + 15 …(i)

Add (i) and (ii)

⇒ b – 9b = – 9a – 15 + a + 15

⇒ –8b = –8a

⇒ a = b

Hence proved

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

RELATED QUESTIONS :